Web-Based Population Cencus Design in Neighborhood Building - Sudarto, Ferry; Yondari, Anisa (Pandawan, 2020)
The population census at the neighborhood level is usually still processed using a manual system. However, the obstacles that arise due to manual processing are quite troublesome, especially when searching for information because the majority of the population works so it is difficult to process data. This study aims to produce an information system for population census management that is faster, more effective, effective and efficient in the neighborhood. The method used in compounding and making this application is by utilizing software development methods, namely the waterfall method which includes analysis, design, coding and testing. The results of this study are the creation of a web to make it easier for residents and heads to manage population censuses, assist in the process of inputting data, searching data, and reporting residents.